Other Societies (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The annual meeting of the Mining and Metallurgical Society of America was held on Tuesday, Jan. 8, 1918, at the Engineers' Club, New York, to elect officers and councillors for the ensuing year, to receive the reports of its retiring officers, and for the transaction of any business which might properly be considered. As usual, the meeting was divided into two sessions; the first, more properly the business session, was called to order at 2:30 p.m., with an attendance of 17 members; the second session took place at 8:30 p. m., immediately following an informal dinner, at which 40 guests and members participated. The latter was particularly interesting because it gave the meeting an opportunity to absorb first-hand information regarding the present crisis in Russia. Messrs. F. W. Draper and J. P. Hutchins, the latter a member and long resident in Russia, were the speakers of the evening.